Improvement of Quality Control in Retail-Type Works Through the Application of the BIM-LC Work Model - Fiorella, Jesús Robles Ana Victoria (2023)
The essence of this research is the development of a working model in which two fundamental tools that control the quality of a finished product are brought together. In this case, the synergy is between the BIM methodology and the Lean Construction philosophy, which will be applied together to improve the quality control of the finished product of a retail construction project. Retail projects which are large investment projects, for which the owners demand high quality in the final product. The work model proposed in this study aims to solve the problem of customer dissatisfaction or dissatisfaction with the final product of a retail construction project. The disagreement on the part of the end user is mainly due to poor quality control during all stages of the project. Based on academic articles and previous studies, a procedure will be proposed in which both the Lean Construction tools are applied, as well as the technology offered by the BIM methodology. Study cases, national and international projects in which this synergy has been applied will be studied and analyzed. Finally, the procedure will be validated by approval of an expert judgment; In other words, BIM managers, engineers, and architects with experience in the application of this synergy, will include their observations, proposals for improvement and recommendations that they contribute to the present investigation.